Investigation of cultural intelligence levels of Selçuk University Erasmus students who have been abroad - Havva Demırel; Hayri Demır (Türk Spor ve Egzersiz Dergisi)
Erasmus exchange program, which started in 1987 in Europe and in which Turkey started participating in 2004, aims at increasing the quality of higher education in Europe and the mobility among teaching staff. The purpose of the present study is defining the levels of adapting cultural differences in foreign countries and establishing effective communication of Selcuk University students, who have been abroad through Erasmus Program. Data of the study were collected from 122 students, who have been abroad as Erasmus students. For data collection, Cultural Intelligence Scale (CQS), which was adapted to Turkish by Ilhan amp; Cetin in 2014 and has dimensions, such as cognition, meta-cognition, motivation and behaviour, was employed. According to the findings, there are significant differences across genders in all dimensions; the number of foreign languages they can speak has effects on the meta-cognition and cognition dimensions; while there aren’t any significant differences in terms of educational status.